ANALISIS VARIABEL PEMBELAJARAN BERDASARKAN TEORI REIGELUTH (Studi pada Mahasiswa Pendidikan Matematika FTIK IAIN Langsa) - Srimuliati, Srimuliati (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2019)
Learning is an attempt to compare what behaviors might occur before individuals are placed in learning situations and what behaviors can be demonstrated after being given treatment. The purpose of this study was to analyze the learning variables according to teroi reigeluth which were divided into 3 things, namely (1) learning conditions, (2) learning methods and (3) learning outcomes. Subjects in this study were students of Mathematics Education Study Program FTIK IAIN Langsa in semester IV unit 1 who took courses in calculus and probability theory. By using descriptive analysis the results and research findings obtained in the form of learning conditions (learning objectives and characters, learner characters, and constraints in learning) for both courses namely calculus and opportunity theory give different results. Fundamental differences related to the two materials provide a finding that students are lacking in reasoning and sharpening their thinking power both through reading and discussing mathematical problems so that they are often wrong in interpreting story problems on occasion. Learning outcomes for both courses are in very good categories for calculus and good for probability theory.